SISTEM INFORMASI PEMESANAN JASA ONLINE BERBASIS WEB STUDI KASUS KABUPATEN JOMBANG - Wahyu Aji Tri Riswandhana; Primaadi Airlangga (KH. A. Wahab Hasbullah University, 2019)
One of the causes of high unemployment is because job seekers only focus on looking for work without realizing the opportunities around them while electronic equipment, household activities, and transportation are secondary needs in daily life, which are complementary to basic needs or needs. primary. When it is damaged or there is no free time to fix it, it will disrupt daily activities. These things require a technician to repair and run them, moreover, many people have expertise in these fields but have not had jobs because of the company's high qualifications. Therefore a system design is needed that can facilitate the search for technical services as well as a place for people who have expertise in their fields. So from these problems, a system is designed that is useful as a place or container for ordering services and service providers to find and channel their expertise. Keywords: Systems, Information, Reservations, Services, Online